2021
DOI: 10.1111/jcpe.13420
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal diseases and depression: A pre‐clinical in vivo study

Abstract: Aim: To analyse, through a pre-clinical in vivo model, the possible mechanisms linking depression and periodontitis at behavioural, microbiological and molecular levels.Materials and methods: Periodontitis (P) was induced in Wistar:Han rats (oral gavages with Porphyromonas gingivalis and Fusobacterium nucleatum) during 12 weeks, followed by a 3-week period of Chronic Mild Stress (CMS) induction. Four groups (n = 12 rats/group) were obtained: periodontitis and CMS (P+CMS+); periodontitis without CMS; CMS withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 62 publications
2
39
0
3
Order By: Relevance
“… See appendix 3a. Martínez et al. (2021) , Spain 47: 11 controls; 12 IPD; 12 MD; 12 IPD ​+ ​MD Rats, 0% female Animals with induced periodontitis or depressive-like behavior alone or in combination Rat model of periodontitis induced by oral inoculation of P. gingivalis and F. nucleatum Experimental depression model using chronic mild stress +ve Rats with IPD and depressive-like behavior had significantly higher GI values compared to non-depressed rats.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… See appendix 3a. Martínez et al. (2021) , Spain 47: 11 controls; 12 IPD; 12 MD; 12 IPD ​+ ​MD Rats, 0% female Animals with induced periodontitis or depressive-like behavior alone or in combination Rat model of periodontitis induced by oral inoculation of P. gingivalis and F. nucleatum Experimental depression model using chronic mild stress +ve Rats with IPD and depressive-like behavior had significantly higher GI values compared to non-depressed rats.…”
Section: Resultsmentioning
confidence: 99%
“…TGF-β levels (pg/ml) in depression group (male 56 ​± ​3; female 51 ​± ​5) vs. healthy control group (male: 63 ​± ​7, female 58 ​± ​7); However, cortisol, IL-10 and TNF-α levels did not differ by depression status. Martínez et al. (2021) Corticosterone, GR receptor, LPS and 16S rRNA genes of P. gingivalis , F. nucleatum, LPS binding protein, TNF-α, IL-1β, NF-kB (p65 subunit), TLR-4, iNOS, mPGES, phosphor p38 MAPKa/b subunit, APO -A1 phospho-mTOR/mTOR ratio Plasma, frontal cortex (nuclear extract or homogenate)/ELISA, RT-PCR, Western blot Rats with depression like behavior had significantly upregulated expression of pro-inflammatory mediators (TNF-α, IL-1β, TRL-4, iNOS and p-p38) in the brain compared to controls.…”
Section: Resultsmentioning
confidence: 99%
“…Several mechanisms have been suggested to link depression and anxiety to periodontitis. Indeed, neuroinflammation sustained by the chronic inflammation associated with periodontitis, increased systemic lipopolysaccharide and bacterial translocation from periodontal sites through a more permeable blood-brain barrier has been investigated [50,51]. The development of depression-like behavior with brain modifications was observed in mice with experimental periodontitis induced by oral gavage of Porphyromonas gingivalis, such as an increased number of activated astrocytes and decreased levels of mature brainderived neurotrophic factor and astrocytic p75NTR in the hippocampus [52].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown elevated expression of NF-κB in the ligature-induced periodontitis and periimplantitis mice models, 41 and in a rat model of bacteriainduced periodontitis. 42 Lei et al demonstrated that after stroke, the activation of epinephrine induced the expression of cAMP that upregulated the level of PKA, followed by the downregulation of the level of NF-κB and weakening the proinflammatory effect of NF-κB. 43 Xu et al observed that in AlCl 3 -stimulated rat lymphocytes, the intracellular content of cAMP was increased, and the mRNA expression level of PKA was increased.…”
Section: Discussionmentioning
confidence: 99%